Testing and verification of a novel single-channel IGBT driver circuit - Lukić, Milan V.; Ninković, Predrag (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
This paper presents a novel single-channel IGBT driver circuit together with a procedure for testing and verification. It is based on a specialized integrated circuit with complete range of protective functions. Experiments are performed to test and verify its behaviour. Experimental results are presented in the form of oscilloscope recordings. It is concluded that the new driver circuit is compatible with modern IGBT transistors and power converter demands and that it can be applied in new designs. It is a part of new 20kW industrial-grade boost converter